Residual stresses and microstructure in Powder Bed Direct Laser Deposition (PB DLD) samples - Song, X; Xie, M; Hofmann, F; Illston, T; Connolley, T; Reinhard, C; Atwood, R; Connor, L; Drakopoulos, M; Frampton, L; Korsunsky, A (Springer Paris, 2015)
In the present study, residual stresses in the Powder Bed Direct Laser Deposition (PB DLD) built parts were investigated using X-ray diffraction strain measurement and finite element simulation. The microstructure and texture of the DLD built parts were studied, indicating that the vertically elongated grains have preferred orientation of (001)-type pointing in the growth direction in the nickel superalloy C263. A conceptual model of residual stress generation was proposed using fictitious thermal expansion based on the argument that residual stresses arise from strain incompatibility that is "frozen in" within the work piece during fabrication.